Retention Program Recommedation for Improving Customer Loyalty at PT INDOSAT Bandung - Fitriyani, Fitri; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2013)
Telecommunications business industry is business that have rapid development with higher competition between provider in Indonesia. PT. Indosat is a telecommunications service company that has been established since 1967 and is the second largest telecom operator in Indonesia. Final data in 2011 showed that the customer churn rate Bandung in November is 18% and in December is 16% . It is shows that the customer churn rate is high. To reduce the churn rate, PT. Indosat should reduce the number deletion by arrange retention programs that can increase customer loyalty. To find out the cause of the problem, research performed by doing external analysis, internal analysis, and analysis of service profit chain in PT. Indosat. Based on the analysis, the root of the problem that caused the high churn rate contained in the products, people, place, price, promotion and process. The next step is to distribute 100 questionnaires regarding SERVQUAL by including attributes the root cause. The results of the questionnaire are then processed by the method of IPA (Index Performance Analysis) Matrix, and obtained three factors that should be prioritized for repairs, the People, Promotion, and Product (Network). Proposed solutions to improve the factor that causing customer churn is done by creating a program implemented by the Division of Customer Service and Retention Indosat. The end result of this study is to provide improvements to the factors that lead to customer dissatisfaction with the program and implementation plan to improve customer satisfaction. With the proposal given the expected level of churn rate in PT. Indosat Bandung will decrease.Â Â Keywords: PT.Indosat Bandung, Telecommunications, Retention Program, Customer Loyalty,Â